Purchasing Decision Mediates Halal Awareness and Brand Image on Viva Cosmetics Customer Satisfaction - Berliana May; Khusnul Fikriyah (International Conference on Islamic Economic (ICIE), 2026)
This study aims to examine the mediating role of purchase decisions in the relationship between halal awareness, brand image, and customer satisfaction of Viva Cosmetics. A quantitative approach was employed using primary data collected through online questionnaires from 151 Muslim consumers of Viva Cosmetics in Surabaya selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that halal awareness positively affects purchase decisions (β = 0.275, t = 3.446, p = 0.001), while brand image has a stronger positive effect on purchase decisions (β = 0.584, t = 7.151, p < 0.001). Purchase decisions significantly influence customer satisfaction (β = 0.254, t = 2.448, p = 0.014). Direct effects also show that halal awareness (β = 0.375, t = 2.825, p = 0.005) and brand image (β = 0.255, t = 2.247, p = 0.025) positively influence customer satisfaction. Mediation analysis reveals that purchase decisions do not significantly mediate the relationship between halal awareness and customer satisfaction (β = 0.070, t = 1.657, p = 0.098), whereas they significantly mediate the relationship between brand image and customer satisfaction (β = 0.148, t = 2.320, p = 0.020). The structural model explains 62.4% of the variance in purchase decisions (R² = 0.624) and 61.6% of the variance in customer satisfaction (R² = 0.616). These findings highlight the more substantial role of brand image than halal awareness in enhancing customer satisfaction through purchase decisions.